Investigation of fluid dynamics in microfracture channels - Mammadova, Maleyka (Eastern-European Journal of Enterprise Technologies, 2022)
The object of the work is an experimental study of the features of the movement of viscous and anomalous fluids in plane-parallel and plane-radial microcracks. In the work, the unexplored problem of hydrodynamic features of fluid motion in the considered objects – channels is solved. It was experimentally revealed that various fluids, when moving in microcracked channels with micron-sized openings, acquire new mechanical properties, which differ from their properties in the usual condition. The effect in the “microcrack-fluid” system is the reason for changes in the mechanical properties of fluids in microcracks and equivalent ultra-low-permeable porous media. It was revealed that when a one-parameter viscous fluid moves in a crack with an opening h<hcr, it becomes two-parameter, i.e. behaves like an anomalous fluid, and when moving with an opening h≥hcr, it restores one-parameter properties, and the anomalous fluid behaves like an anomalous fluid but increases the rheological constants of the model. The results of the research require taking into consideration the crack effect in estimating the parameters of the technological processes system and technical devices “microcrack-fluid”. Machines and mechanisms must additionally have nodes that would prevent this effect. This is of scientific and practical importance for various fields of the industry, machine manufacturing, instrument manufacturing, chemical technology and medicine.